41 From paper to paperless: do electronic systems ensure safe and effective communication and documentation of do not attempt cardio-pulmonary resuscitation (DNACPR) decisions?. (13th October 2019) - Harrington, Laura; Price, Kathryn; Edmonds, Polly
Abstract : Introduction and aim: With NHS Trusts making the transition from paper to paperless; it is vital that integration of electronic systems are safe for patients. Following introduction of an electronic-DNACPR toolbar, this project aimed to improve the quality of documentation and communication of DNACPR decisions. Method: A singled centered, closed loop quality improvement project was performed January - June 2018 including all inpatients with a DNACPR on three gerontology wards. Data was collected over a four week period. The DNACPR toolbar, e-form, medical notes and discharge letters were reviewed. The documentation of discussions with patients, families, senior doctors, nursing staff and the MDT were recorded. Retrospective discharge analysis was performed to review communication to the GP. Chi Squared analysis was used to assess statistical significance of the raw measure improvements after the second cycle. Interventions : (Figure 1) Results : (Figure 2) January cycle, all 181 patients had a resuscitation status and treatment escalation plan (TEP). 73% had a DNACPR (86% by senior doctor). 85% had a valid e-form. 68% evidenced a discussion patients/relatives, 13% had a documented discussion with the MDT. 79% were communicated on discharge through comprehensive geriatric assessment (CGA). Following interventions, all measures improved. Of 176 patients; 72% a DNACPR decision (93% by senior doctor), 100% an e-form. 71% evidenced discussion with patients/relatives, 57% had documented discussion with the MDT. Conclusion: A critical finding was poor communication, increasing risk of inappropriate resuscitation. Process revision and staff training has led to improved communication and documentation, increasing patient safety. DNACPR decision inclusion in discharge letters via CGAs has improved care co-ordination on discharge.